2020
DOI: 10.3390/nu12020476
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced GIP Secretion in Obesity Is Associated with Biochemical Alteration and miRNA Contribution to the Development of Liver Steatosis

Abstract: Nutrient excess enhances glucose-dependent insulinotropic polypeptide (GIP) secretion, which may in turn contribute to the development of liver steatosis. We hypothesized that elevated GIP levels in obesity may affect markers of liver injury through microRNAs. The study involved 128 subjects (body mass index (BMI) 25–40). Fasting and postprandial GIP, glucose, insulin, and lipids, as well as fasting alanine aminotransferase (ALT), γ-glutamyltransferase (GGT), cytokeratin-18, fibroblast growth factor (FGF)-19, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 96 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…1978; Góralska et al . 2020). Interestingly, mice lacking the GIP receptor are protected against high fat diet‐induced obesity and insulin resistance (Miyawaki et al .…”
Section: Discussionmentioning
confidence: 99%
“…1978; Góralska et al . 2020). Interestingly, mice lacking the GIP receptor are protected against high fat diet‐induced obesity and insulin resistance (Miyawaki et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that miR-381-3p was a dual inhibitor of apoptosis and necrosis, and it could also regulate downstream target genes to inhibit smooth muscle growth of human ( 46 ). However, miR-136 may be related to fat metabolism, one of the evidence is that overexpression of miR-136 could inhibit the expression of LRH-1 and lead to dyslipidemia and liver steatosis ( 47 ). The results of this study showed that MSTRG.41.1-miR and XR_001040849.2 regulated miR-381-3p and miR-136, respectively, relieved the inhibition of GPD2 by miRNA, and played an important biological role in fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some improvements in metabolic risk factors, associated with the reduction in liver enzymes and liver fat content were revealed by meta-analysis of controlled studies on the effectiveness of long-chain n-3 fatty acids in patients with nonalcoholic fatty liver disease (NAFLD) [ 10 ]. Our previously published data show an association of high GIP levels in obese subjects with elevated liver enzymes, accompanied by an altered miRNA profile characteristic of hepatic and lipid complications of obesity [ 16 ]. Thus, the improvement in insulin sensitivity with a reduction in circulating NEFAs due to n-3 PUFA supplementation observed in our study suggests that there is a reduction in NAFLD risk factors in obese patients with high GIP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous data indicate the association of plasma GIP levels not only with glucose metabolism but also fasting lipids, chronic inflammation, and liver function [ 15 , 16 ]. The mechanism underlying associations of GIP with lipid metabolism warrants further study, especially in the light of the development of new incretin-based pharmacotherapies for the treatment of obesity, dual GIP and GLP-1 receptor agonists.…”
Section: Introductionmentioning
confidence: 99%